F11 Prevalence of cigarette smoking in huntington's disease. (September 2018) - Scott, Natasha; Kumar, Anagha; Kuprewicz, Robin; Anderson, Karen
Abstract : Background: There is some evidence that Huntington's Disease (HD) patients are more likely to consume cigarettes than the general population. Aims: To compare the prevalence of cigarette smoking within four different groups of Enroll-HD subjects (manifest HD, pre-manifest HD, genotype negative, and family controls) and to compare Unified Huntington's Disease Rating Scale Total Motor Score (UHDRS-TMS) between smokers and non-smokers to determine whether motor symptom level is related to cigarette use. Methods/techniques: The percentage of smokers versus non-smokers within each group of Enroll-HD subjects was calculated. 'Smoker' was defined as any participant who used 1 or more cigarettes daily in the past year. Percentage of smokers within all gene negative groups combined was also calculated. A p-value hypothesis test was done to test statistical significance. The average TMS score on the UHDRS motor exam was calculated for both smokers and non-smokers and a two-tailed, two sample unequal variance t-test was done. Results/outcome: The percentage of smokers within manifest HD, pre-manifest HD, genotype negative, and family control groups were 25.8%, 22.7%, 18.5%, and 15.6%, respectively (p-value<0.0000007) The percentage of smokers in all HD negative groups combined was 19.6% (p-value<0.000004) The average TMS score was 35.98 for smokers and 40.91 for non-smokers. The results of the t-test were 0.0000005296. Conclusions: It was determined that there is a statistically significant difference between the number of smokers in each Enroll-HD group, and that the prevalence of smokers within HD-manifest patients is significantly higher. It was also determined that non-smokers had more motor symptoms, on average. It is unclear from these data whether this difference comes from patients who quit smoking because of HD motor symptoms or if smokers are more likely to seek medical care.